Novel gene cassettes and integrons in antibiotic-resistant bacteria isolated from urban wastewaters - Moura, Alexandra (2019)
In this study, the occurrence and diversity of integrons were evaluated in 697 isolates belonging to Enterobacteriaceae and Aeromonas spp. isolated from urban wastewaters. Screening of integrons was performed by dot blot hybridization and intI-positive strains were further characterized. The global prevalence of integrons was 3.73%. Three new gene cassettes were identified: a novel aadA variant (aadA17), a gene putatively involved in cell signaling (dcyA) and an open reading frame of unknown function interrupted by a novel insertion sequence (orfER.17::ISAs12). In total, thirteen different gene cassette arrays were detected, 4 representing novel integrons: intI1-dcyA-tniC, intI1-orfER.1.7::ISAs12-aadA13-qacEΔ1-sul1, intI1-aacA4-catB3-bla(OxA-10)-aadA1-qacEΔ1-sul1 and intI1-catB8-aadA17-qacEΔ1-sul1. Approximately 80% of strains were resistant to at least 3 antibiotics of different classes. The presence of novel integron structures in treated effluents suggests that domestic wastewaters may favor the formation of novel combinations of gene cassettes. Moreover, the high prevalence of multiresistant strains highlights the urgent need to employ effective means of effluent disinfection to avoid dissemination of antibiotic-resistant bacteria.